High-strength corrugated board and preparation method thereof

By spraying modified wear-resistant coatings with various components such as polyvinylidene fluoride resin on the surface of corrugated cardboard, the wear resistance and strength of corrugated cardboard is improved, and the problem of insufficient wear resistance of corrugated cardboard is solved, and waste recycling is carried out Paper reuse reduces resource waste and production costs.

CN119266027AInactive Publication Date: 2025-01-07ZHUHAI ZHENGYE PACKAGING

Patent Information

Application Number
CN202411476072.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing corrugated cardboard is not wear-resistant when facing weight and pressure, making it difficult to effectively protect packaging items, and it is highly dependent on native wood during the production process, and is wasteful of resources and cost high.

Method used

Spray a modified wear-resistant coating on the surface of corrugated cardboard. The coating consists of polyvinylidene fluoride resin, polymethyl methacrylate, diatomaceous earth, alumina, graphene oxide and carbon nanotubes. Chemical reactions and physical combination form a hard and wear-resistant surface, improving the wear resistance and strength of corrugated cardboard, and reducing dependence on native wood through recycling waste paper.

Benefits of technology

It significantly improves the mechanical strength and wear resistance of corrugated cardboard, can better protect the safety of items in the packaging, and reduces dependence on natural resources and production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005096148700000111
    Figure BDA0005096148700000111
Patent Text Reader

Abstract

The invention relates to a high-strength corrugated board and a preparation method thereof, and belongs to the technical field of corrugated board preparation. In the coating disclosed by the invention, diatomite, aluminum oxide, graphene oxide, rare earth oxide, carbon nanotubes and the like are uniformly mixed through mechanical actions such as ball milling and the like to form a stable solid-liquid mixture. The preparation method comprises the following steps: dissolving polyvinylidene fluoride resin and polymethyl methacrylate in an ethyl acetate solution to form a uniform mixed solution; the organic resin and the inorganic filler are combined through Van der Waals' force, hydrogen bonds and other interaction forces to form a firm coating structure, and through heating and pressure forming of the paperboard and a modified wear-resistant coating sprayed on the surface of the surface paper, a final product has high mechanical strength and wear resistance, and the safety of articles in packages can be better protected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of corrugated paperboard preparation, and relates to a high-strength corrugated paperboard and a preparation method thereof. Background Art

[0002] Corrugated cardboard, also known as corrugated cardboard, is made of at least one layer of corrugated paper and one layer of boxboard paper. It has good elasticity and extensibility and is mainly used to make cartons, carton sandwiches and other packaging materials for fragile goods. Corrugated cardboard is a multi-layer adhesive body, which is composed of at least one layer of wavy core paper and one layer of cardboard. It has high mechanical strength and can withstand collisions and falls during transportation. High-strength corrugated cardboard has good cardboard elasticity, flat compression strength and vertical compression strength, and can withstand greater weight and pressure, effectively protecting the packaged items.

[0003] High-strength corrugated cardboard is widely used in the packaging industry, such as making various cartons, paper boxes, paper pallets and other packaging materials. With the rapid development of e-commerce, express delivery and other industries, its demand continues to increase. Summary of the invention

[0004] The purpose of the present invention is to provide a high-strength corrugated paperboard and a preparation method thereof, which has the characteristics of high strength and good wear resistance.

[0005] A high-strength corrugated paperboard, the corrugated paperboard comprises a base paper, a corrugated paper core and a face paper, the three are bonded by an adhesive, a layer of modified wear-resistant coating is attached to the surface of the face paper, wherein the preparation method of the coating used for the modified wear-resistant coating is as follows:

[0006] S1: dissolving polyvinylidene fluoride resin in ethyl acetate to obtain a mixed solution with a mass fraction of 10-20%, then adding 1-3wt% polymethyl methacrylate, slowly heating to 50°C, and stirring at a speed of 200r / min for 1-2h to obtain a mixed solution A;

[0007] S2: diatomaceous earth and alumina are mixed in a mass ratio of 1:(1-5), and ground in a ball mill at a speed of 400 r / min for 3-4 h to obtain a mixture B;

[0008] S3: dissolving graphene oxide in deionized water to prepare a graphene oxide solution with a mass fraction of 10%, adding mixture B to the graphene oxide solution at a solid-liquid mass ratio of 1:(3-5), and ultrasonicating for 1-2 hours to obtain a solid-liquid mixture C;

[0009] S4: drying the solid-liquid mixture C at 110° C. for 12 h, and then calcining the mixture from room temperature to 400° C. for 3 to 4 h to obtain a mixture D;

[0010] S5: Mix the mixture D, rare earth oxide and carbon nanotube in a mass ratio of 4:1:1, put into a ball mill and grind at a speed of 500 r / min for 1 to 2 h to obtain a mixture E;

[0011] S6: Heat the mixture solution A to 70°C, stir at a speed of 150 r / min, add mixture E while stirring, the solid-liquid mass ratio of the mixture solution A to the mixture E is 1:1, stir for 0.5 h, cool to room temperature, continue stirring at a speed of 200 r / min for 1 to 2 h at room temperature, and obtain the coating used for the modified wear-resistant coating.

[0012] Furthermore, the adhesive is one of XK-20 and HM-M726.

[0013] Furthermore, the rate of heating from room temperature to 400° C. in S4 is 5° C. / min.

[0014] Furthermore, the rare earth oxide in S5 is one or more of cerium oxide, lanthanum oxide, and praseodymium oxide.

[0015] Furthermore, the particle size of the mixture E in S5 is 300 mesh.

[0016] The preparation method of the high-strength corrugated paperboard is specifically as follows:

[0017] S6.1: Shred the recovered waste paper, soak the shredded paper in 80°C water to soften it for 12 hours, and filter it;

[0018] S6.2: Put the paper obtained after softening and filtering into a pulping machine for kneading and grinding treatment, the speed of the pulping machine is 1450r / min, the treatment time is 2h, and a uniform paper paste is obtained;

[0019] S6.3: Add 2 wt% polyacrylamide resin to the paper paste, stir at a speed of 400 r / min for 2 h to obtain pulp, put the pulp into a paper machine for dehydration and press to obtain a flat paperboard, the thickness of the flat paper is 2 mm;

[0020] S6.4: Put the pulp into a corrugated paper core making machine, and after heating, pressurizing and forming, make a corrugated paper core with a concave and convex corrugated shape, and the thickness of the corrugated paper core is 3mm;

[0021] S6.5: Adhesive is used to stick flat cardboard on both sides of the corrugated paper core to obtain corrugated cardboard, and a modified wear-resistant coating is sprayed on the surface of the face paper with a coating thickness of 10 μm. After drying by laser drying method, the high-strength corrugated cardboard is obtained.

[0022] Furthermore, in said S6.3, the pressure of the paper machine is 8-10 MPa, and the temperature is 70-90°C.

[0023] Furthermore, in S6.4, the pressure is 7 MPa and the temperature is 80°C.

[0024] Furthermore, the spraying parameters of the modified wear-resistant coating in S6.5 are spraying distance 60 mm and spraying rate 50 mm / s.

[0025] Furthermore, the parameters of the laser drying in S6.5 are: laser power 200 W, temperature 80° C., and irradiation time 40 min.

[0026] In order to improve the strength of corrugated paperboard, the present invention sprays a modified wear-resistant coating on the surface of the surface paper. The various components in the coating, such as polyvinylidene fluoride resin, polymethyl methacrylate, diatomaceous earth, aluminum oxide, graphene oxide, rare earth oxide and carbon nanotubes, work together to form a hard and friction-resistant surface, thereby effectively improving the wear resistance and strength of the corrugated paperboard.

[0027] A strong coating structure is formed through chemical reaction and physical combination between the components, which ensures good adhesion between the coating and the surface paper, while improving the chemical stability and thermal stability of the coating.

[0028] Polyvinylidene fluoride resin, as the main film-forming material of the coating, provides the basic mechanical properties and chemical corrosion resistance of the coating; polymethyl methacrylate can enhance the hardness and wear resistance of the coating, while improving the flexibility and glossiness of the coating; diatomaceous earth and alumina, as inorganic fillers, can further increase the hardness and wear resistance of the coating, while improving the thermal stability and chemical stability of the coating; graphene oxide uses its excellent mechanical properties and two-dimensional lamellar structure to enhance the mechanical strength and wear resistance of the coating, while promoting the uniform dispersion and bonding between the components; rare earth oxides improve the weather resistance and corrosion resistance of the coating through their special electronic structure and catalytic properties; carbon nanotubes, as nano-scale reinforcing materials, significantly improve the mechanical properties and conductive properties of the coating, and further enhance the wear resistance and comprehensive performance of the coating.

[0029] Polyvinylidene fluoride resin is known for its excellent chemical resistance, heat resistance and weather resistance, while polymethyl methacrylate has good hardness, wear resistance and transparency. After the two are combined, the coating further enhances the hardness and wear resistance of the coating while maintaining the original excellent properties of polyvinylidene fluoride resin. During the curing process of the coating, polyvinylidene fluoride resin and polymethyl methacrylate will undergo a certain degree of orderly phase separation, and stable connection points will be formed at the phase interface through hydrogen bonds and van der Waals forces. These connection points gradually increase and connect with each other as the phase separation proceeds, eventually forming an interpenetrating network structure. This structure enables the coating to disperse stress more effectively when subjected to external forces, thereby improving the wear resistance and impact resistance of the coating.

[0030] In the coating of the present invention, diatomite, aluminum oxide, graphene oxide, rare earth oxide and carbon nanotubes are uniformly mixed by mechanical action such as ball milling to form a stable solid-liquid mixture. Polyvinylidene fluoride resin and polymethyl methacrylate are dissolved in ethyl acetate solution to form a uniform mixed solution. These organic resins and inorganic fillers are combined by interaction forces such as van der Waals force and hydrogen bond to form a firm coating structure. In addition, the special two-dimensional sheet structure of graphene oxide helps to promote uniform dispersion and combination between the components.

[0031] The resin in the present invention provides the basic mechanical properties and film-forming property of the coating, while the inorganic filler enhances the hardness and wear resistance of the coating through its unique physical and chemical properties. This complementarity enables the coating to exhibit excellent comprehensive properties in many aspects.

[0032] The inorganic filler and the resin matrix form a strong interface bond through chemical bonding, physical adsorption and mechanical interlocking. This bonding force helps prevent the coating from peeling or delamination during use.

[0033] The addition of inorganic fillers can refine the grain structure of the resin matrix and reduce internal defects, thereby improving the density and uniformity of the coating. In addition, graphene oxide can also form a two-dimensional network structure in the coating, further enhancing the mechanical properties of the coating. As a two-dimensional nanomaterial, graphene oxide has extremely high mechanical strength and hardness. Loading it on the surface of diatomaceous earth and alumina can significantly improve the hardness and wear resistance of the composite material, thereby protecting the corrugated cardboard from external mechanical wear. The functional groups on the surface of graphene oxide can interact with groups such as hydroxyl groups on the surface of diatomaceous earth and alumina to form stable chemical bonds, thereby enhancing the interfacial bonding between the filler and the resin matrix and preventing the coating from peeling off or stratification during use. The good dispersibility of graphene oxide helps it to be evenly loaded on the surface of diatomaceous earth and alumina, thereby avoiding the agglomeration of fillers in the resin matrix and improving the uniformity and consistency of the coating.

[0034] The interface area between the resin and the inorganic filler is affected by the interfacial tension and charge distribution. These interfacial effects can affect the dispersion state and bonding mode of the filler in the resin matrix, thus having an important impact on the performance of the coating. By optimizing the interfacial effect, the comprehensive performance of the coating can be further improved; in addition, when the inorganic filler is dispersed in the resin matrix at the nanoscale, a significant nano effect will be produced. This effect includes surface effect, small size effect and quantum size effect, which can significantly enhance the mechanical properties, optical properties and thermal stability of the coating.

[0035] The preparation process of the present invention starts with recycled waste paper, and through the steps of crushing, softening, pulping, etc., the waste paper resources are reused, the dependence on native wood is reduced, and it is helpful to save natural resources and reduce production costs. By heating and pressurizing the cardboard and spraying a modified wear-resistant coating on the surface of the face paper, the final product has higher mechanical strength and wear resistance, and can better protect the safety of the items in the package.

[0036] Beneficial effects of the present invention:

[0037] (1) In the coating of the present invention, diatomaceous earth, aluminum oxide, graphene oxide, rare earth oxide and carbon nanotubes are uniformly mixed by mechanical action such as ball milling to form a stable solid-liquid mixture. Polyvinylidene fluoride resin and polymethyl methacrylate are dissolved in ethyl acetate solution to form a uniform mixed solution; these organic resins and inorganic fillers are combined by interaction forces such as van der Waals force and hydrogen bond to form a firm coating structure;

[0038] (2) The preparation process of the present invention starts with recycled waste paper and realizes the reuse of waste paper resources through the steps of crushing, softening, pulping, etc., reducing the dependence on native wood, helping to save natural resources and reduce production costs. By heating and pressurizing the cardboard and spraying a modified wear-resistant coating on the surface of the face paper, the final product has higher mechanical strength and wear resistance, which can better protect the safety of the items in the package. DETAILED DESCRIPTION

[0039] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0040] The polyvinylidene fluoride resin used in the present invention was purchased from Tianjin Xiensi Biochemical Technology Co., Ltd. with a product number of P-85140; the polymethyl methacrylate used in the present invention was purchased from Shanghai Yien Chemical Technology Co., Ltd. with a product number of R007432.

[0041] Example 1

[0042] The preparation method of the coating used for the modified wear-resistant coating is as follows:

[0043] S1: dissolving polyvinylidene fluoride resin in ethyl acetate to obtain a mixed solution with a mass fraction of 20%, then adding 3wt% polymethyl methacrylate, slowly heating to 50°C, and stirring at a speed of 200r / min for 2h to obtain a mixed solution A;

[0044] S2: diatomaceous earth and alumina were mixed in a mass ratio of 1:3, and ground in a ball mill at a speed of 400 r / min for 4 h to obtain a mixture B;

[0045] S3: dissolving graphene oxide in deionized water to prepare a graphene oxide solution with a mass fraction of 10%, adding mixture B to the graphene oxide solution at a solid-liquid mass ratio of 1:4, and ultrasonicating for 2 hours to obtain a solid-liquid mixture C;

[0046] S4: drying the solid-liquid mixture C at 110° C. for 12 h, and then heating the mixture from room temperature to 400° C. for calcination at a heating rate of 5° C. / min for 3 to 4 h to obtain a mixture D;

[0047] S5: Mix the mixture D, cerium oxide and carbon nanotubes in a mass ratio of 4:1:1, put them into a ball mill and grind them at a speed of 500 r / min for 2 h to obtain a mixture E, wherein the particle size of the mixture E is 300 mesh;

[0048] S6: Heat the mixture solution A to 70°C, stir at a speed of 150 r / min, add mixture E while stirring, the solid-liquid mass ratio of the mixture solution A to the mixture E is 1:1, stir for 0.5 h, cool to room temperature, continue stirring at a speed of 200 r / min for 1 to 2 h at room temperature, and obtain the coating used for the modified wear-resistant coating.

[0049] The preparation method of the high-strength corrugated paperboard is specifically as follows:

[0050] S6.1: Shred the recovered waste paper, soak the shredded paper in 80°C water to soften it for 12 hours, and filter it;

[0051] S6.2: Put the paper obtained after softening and filtering into a pulping machine for kneading and grinding treatment, the speed of the pulping machine is 1450r / min, the treatment time is 2h, and a uniform paper paste is obtained;

[0052] S6.3: Add 2 wt% polyacrylamide resin to the paper paste, stir at a speed of 400 r / min for 2 h to obtain paper pulp, put the paper pulp into a paper machine for dehydration and press to obtain a flat paperboard, the thickness of the flat paper is 2 mm, the pressure of the paper machine is 9 MPa, and the temperature is 80°C;

[0053] S6.4: placing the pulp into a corrugated paper core making machine, molding at 80° C. and a pressure of 7 MPa to make a corrugated paper core having a concave-convex corrugated shape, wherein the thickness of the corrugated paper core is 3 mm;

[0054] S6.5: Adhesive XK-20 is used to stick flat cardboard on both sides of the corrugated paper core to obtain corrugated cardboard, and a modified wear-resistant coating is sprayed on the surface of the face paper. The spraying parameters are spraying distance 60 mm, spraying rate 50 mm / s, and after drying by laser drying method, the laser drying parameters are laser power 200 W, temperature 80°C, irradiation time 40 min, and coating thickness 10 μm, to obtain the high-strength corrugated cardboard.

[0055] Example 2

[0056] The preparation method of the coating used for the modified wear-resistant coating is as follows:

[0057] S1: dissolving polyvinylidene fluoride resin in ethyl acetate to obtain a mixed solution with a mass fraction of 15%, then adding 2wt% polymethyl methacrylate, slowly heating to 50°C, and stirring at a speed of 200r / min for 1h to obtain a mixed solution A;

[0058] S2: diatomaceous earth and alumina were mixed in a mass ratio of 1:5, and ground in a ball mill at a speed of 400 r / min for 3 h to obtain a mixture B;

[0059] S3: dissolving graphene oxide in deionized water to prepare a graphene oxide solution with a mass fraction of 10%, adding mixture B to the graphene oxide solution at a solid-liquid mass ratio of 1:5, and ultrasonicating for 1 hour to obtain a solid-liquid mixture C;

[0060] S4: drying the solid-liquid mixture C at 110° C. for 12 h, and then heating the mixture from room temperature to 400° C. for calcination at a heating rate of 5° C. / min for 3 h to obtain a mixture D;

[0061] S5: Mix the mixture D with lanthanum oxide and carbon nanotubes in a mass ratio of 4:1:1, put them into a ball mill and grind them at a speed of 500 r / min for 1 h to obtain a mixture E, wherein the particle size of the mixture E is 300 mesh;

[0062] S6: Heat the mixture solution A to 70°C, stir at a speed of 150 r / min, add mixture E while stirring, the solid-liquid mass ratio of the mixture solution A to the mixture E is 1:1, stir for 0.5 h, cool to room temperature, continue stirring at room temperature at a speed of 200 r / min for 1 h, and obtain the coating used for the modified wear-resistant coating.

[0063] The preparation method of the high-strength corrugated paperboard is specifically as follows:

[0064] S6.1: Shred the recovered waste paper, soak the shredded paper in 80°C water to soften it for 12 hours, and filter it;

[0065] S6.2: Put the paper obtained after softening and filtering into a pulping machine for kneading and grinding treatment, the speed of the pulping machine is 1450r / min, the treatment time is 2h, and a uniform paper paste is obtained;

[0066] S6.3: Add 2 wt% polyacrylamide resin to the paper paste, stir at a speed of 400 r / min for 2 h to obtain pulp, put the pulp into a paper machine for dehydration and press to obtain a flat paperboard, the thickness of the flat paper is 2 mm, the pressure of the paper machine is 8 MPa, and the temperature is 70°C;

[0067] S6.4: placing the pulp into a corrugated paper core making machine, molding at 80° C. and a pressure of 7 MPa to make a corrugated paper core having a concave-convex corrugated shape, wherein the thickness of the corrugated paper core is 3 mm;

[0068] S6.5: Use adhesive HM-M726 to stick flat cardboard on both sides of the corrugated paper core to obtain corrugated cardboard, spray a modified wear-resistant coating on the surface of the face paper, the spraying parameters are spraying distance 60mm, spraying rate 50mm / s, and after drying by laser drying method, the laser drying parameters are laser power 200W, temperature 80℃, irradiation time 40min, coating thickness 10μm, to obtain the high-strength corrugated cardboard.

[0069] Example 3

[0070] The preparation method of the coating used for the modified wear-resistant coating is as follows:

[0071] S1: dissolving polyvinylidene fluoride resin in ethyl acetate to obtain a mixed solution with a mass fraction of 10%, then adding 1wt% polymethyl methacrylate, slowly heating to 50°C, and stirring at a speed of 200r / min for 1h to obtain a mixed solution A;

[0072] S2: diatomaceous earth and alumina were mixed in a mass ratio of 1:1, and ground in a ball mill at a speed of 400 r / min for 3 h to obtain a mixture B;

[0073] S3: dissolving graphene oxide in deionized water to prepare a graphene oxide solution with a mass fraction of 10%, adding mixture B to the graphene oxide solution with a solid-liquid mass ratio of 1:3, and after ultrasonic treatment for 1 hour, obtaining a solid-liquid mixture C;

[0074] S4: drying the solid-liquid mixture C at 110° C. for 12 h, and then heating the mixture from room temperature to 400° C. for calcination at a heating rate of 5° C. / min for 4 h to obtain a mixture D;

[0075] S5: Mix the mixture D, praseodymium oxide and carbon nanotubes in a mass ratio of 4:1:1, put them into a ball mill and grind them at a speed of 500 r / min for 1 h to obtain a mixture E, wherein the particle size of the mixture E is 300 mesh;

[0076] S6: Heat the mixture solution A to 70°C, stir at a speed of 150 r / min, add mixture E while stirring, the solid-liquid mass ratio of the mixture solution A to the mixture E is 1:1, stir for 0.5 h, cool to room temperature, continue stirring at room temperature at a speed of 200 r / min for 1 h, and obtain the coating used for the modified wear-resistant coating.

[0077] The preparation method of the high-strength corrugated paperboard is specifically as follows:

[0078] S6.1: Shred the recovered waste paper, soak the shredded paper in 80°C water to soften it for 12 hours, and filter it;

[0079] S6.2: Put the paper obtained after softening and filtering into a pulping machine for kneading and grinding treatment, the speed of the pulping machine is 1450r / min, the treatment time is 2h, and a uniform paper paste is obtained;

[0080] S6.3: Add 2 wt% polyacrylamide resin to the paper paste, stir at a speed of 400 r / min for 2 h to obtain pulp, put the pulp into a paper machine for dehydration and press to obtain a flat paperboard, the thickness of the flat paper is 2 mm, the pressure of the paper machine is 10 MPa, and the temperature is 90°C;

[0081] S6.4: placing the pulp into a corrugated paper core making machine, molding at 80° C. and a pressure of 7 MPa to make a corrugated paper core having a concave-convex corrugated shape, wherein the thickness of the corrugated paper core is 3 mm;

[0082] S6.5: Adhesive XK-20 is used to stick flat cardboard on both sides of the corrugated paper core to obtain corrugated cardboard, and a modified wear-resistant coating is sprayed on the surface of the face paper. The spraying parameters are spraying distance 60 mm, spraying rate 50 mm / s, and after drying by laser drying method, the laser drying parameters are laser power 200 W, temperature 80°C, irradiation time 40 min, and coating thickness 10 μm, to obtain the high-strength corrugated cardboard.

[0083] Comparative Example 1

[0084] In this comparative example, polymethyl methacrylate is not added in the preparation of the modified wear-resistant coating, and the remaining steps are consistent with those of Example 1.

[0085] Comparative Example 2

[0086] In this comparative example, diatomaceous earth and alumina are not added in the preparation of the modified wear-resistant coating, and the remaining steps are consistent with those of Example 1.

[0087] Comparative Example 3

[0088] In this comparative example, graphene oxide is not added in the preparation of the modified wear-resistant coating, and the remaining steps are consistent with Example 1.

[0089] Comparative Example 4

[0090] In this comparative example, no rare earth oxide and carbon nanotubes are added in the preparation of the modified wear-resistant coating, and the remaining steps are consistent with those in Example 1.

[0091] Comparative Example 5

[0092] In this comparative example, in the preparation of the high-strength corrugated paperboard, the modified wear-resistant coating is not sprayed on the surface of the face paper, and the remaining steps are consistent with those of Example 1.

[0093] The surface wear and scratch resistance of the embodiments and comparative examples were tested according to the pencil hardness test of GB / T6739-2006. The pencil was fixed on the device and pressed down on the panel surface at a 45° angle under a load of 500g. The hardness decreased from 3H to 3B. The hardness of the pen tip when a 3mm scratch appeared was recorded, and the scratch resistance was scored.

[0094] Cut the sample into 270*60mm and fix it on the friction table of the equipment; then fix a piece of white paper on a 4-pound load block and place it above the sample, set the friction times to 600 times, 800 times, 1000 times, and 1200 times respectively, and observe the limit number of times when scratches begin to appear after friction;

[0095] The bursting strength test was carried out according to GB / T 6544-2008 standard. The test results are summarized in the following table.

[0096]

[0097] It can be seen from the data of the examples and comparative examples that the addition of polymethyl methacrylate, diatomaceous earth and alumina, graphene oxide, rare earth oxides and carbon nanotubes can effectively improve the strength of corrugated paperboard.

[0098] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A high-strength corrugated paperboard, characterized in that: The corrugated paperboard comprises a base paper, a corrugated paper core and a face paper, the three of which are bonded by an adhesive, and a layer of modified wear-resistant coating is attached to the surface of the face paper, wherein the preparation method of the coating used for the modified wear-resistant coating is as follows: S1: dissolving polyvinylidene fluoride resin in ethyl acetate to obtain a mixed solution with a mass fraction of 10-20%, then adding 1-3wt% polymethyl methacrylate, slowly heating to 50°C at a rate of 2°C / min, and stirring at a speed of 200r / min for 1-2h to obtain a mixed solution A; S2: diatomaceous earth and alumina are mixed in a mass ratio of 1:(1-5), and ground in a ball mill at a speed of 400 r / min for 3-4 h to obtain a mixture B; S3: dissolving graphene oxide in deionized water to prepare a graphene oxide solution with a mass fraction of 10%, adding mixture B to the graphene oxide solution at a solid-liquid mass ratio of 1:(3-5), and ultrasonicating for 1-2 hours to obtain a solid-liquid mixture C; S4: drying the solid-liquid mixture C at 110° C. for 12 h, and then calcining the mixture from room temperature to 400° C. for 3 to 4 h to obtain a mixture D; S5: Mix the mixture D, rare earth oxide and carbon nanotube in a mass ratio of 4:1:1, put into a ball mill and grind at a speed of 500 r / min for 1 to 2 h to obtain a mixture E; S6: Heat the mixture solution A to 70°C, stir at a speed of 150 r / min, add mixture E while stirring, the solid-liquid mass ratio of the mixture solution A to the mixture E is 1:1, stir for 0.5 h, cool to room temperature, continue stirring at a speed of 200 r / min for 1 to 2 h at room temperature, and obtain the coating used for the modified wear-resistant coating.

2. The high-strength corrugated paperboard according to claim 1, characterized in that: The adhesive is one of XK-20 and HM-M726.

3. The high-strength corrugated paperboard according to claim 1, characterized in that: The rate of heating from room temperature to 400° C. in S4 is 5° C. / min.

4. The high-strength corrugated paperboard according to claim 1, characterized in that: The rare earth oxide in S5 is one or more of cerium oxide, lanthanum oxide and praseodymium oxide.

5. The high-strength corrugated paperboard according to claim 1, characterized in that: The particle size of the mixture E in S5 is 300 mesh.

6. A method for preparing a high-strength corrugated paperboard according to any one of claims 1 to 5, characterized in that: The preparation method of the high-strength corrugated paperboard is specifically as follows: S6.1: Shred the recovered waste paper, soak the shredded paper in 80°C water to soften it for 12 hours, and filter it; S6.2: Put the paper obtained after softening and filtering into a pulping machine for kneading and grinding treatment, the speed of the pulping machine is 1450r / min, the treatment time is 2h, and a uniform paper paste is obtained; S6.3: Add 2 wt% polyacrylamide resin to the paper paste, stir at a speed of 400 r / min for 2 h to obtain pulp, put the pulp into a paper machine for dehydration and press to obtain a flat paperboard, the thickness of the flat paper is 2 mm; S6.4: Put the pulp into a corrugated paper core making machine, and after heating, pressurizing and forming, make a corrugated paper core with a concave and convex corrugated shape, and the thickness of the corrugated paper core is 3mm; S6.5: Adhesive is used to stick flat cardboard on both sides of the corrugated paper core to obtain corrugated cardboard, and a modified wear-resistant coating is sprayed on the surface of the face paper with a coating thickness of 10 μm. After drying by laser drying method, the high-strength corrugated cardboard is obtained.

7. The method for preparing high-strength corrugated paperboard according to claim 6, characterized in that: The pressure of the paper machine in S6.3 is 8-10 MPa and the temperature is 70-90°C.

8. The method for preparing high-strength corrugated paperboard according to claim 6, characterized in that: The pressure in S6.4 is 7 MPa and the temperature is 80°C.

9. The method for preparing high-strength corrugated paperboard according to claim 6, characterized in that: The spraying parameters of the modified wear-resistant coating in S6.5 are spraying distance 60 mm and spraying rate 50 mm / s.

10. The method for preparing high-strength corrugated paperboard according to claim 6, characterized in that: The parameters of the laser drying in S6.5 are: laser power 200 W, temperature 80° C., and irradiation time 40 min.

Citation Information

Patent Citations

  • Highly-wear-resistant super-hydrophobic composite coating and preparation method thereof

    CN105419450A

  • Ceramic product with graphene oxide anti-corrosive layer and preparation method of ceramic product

    CN109081680A

  • Electrifying nanofiber filter material for fresh air system and preparation method thereof

    CN109589684A

  • High-wear-resistance polytetrafluoroethylene composite material and preparation method thereof

    CN110105695A

  • Wear-resistant coating for decorative plate and preparation method thereof

    CN110903750A

Cited By

  • Environment-friendly wear-resistant corrugated board and preparation method thereof

    CN121915631A